Obesity-related mortality in France, Italy, and the United States: a comparison using multiple cause-of-death analysis - Barbieri, Magali (Int J Public Health, 2017)
OBJECTIVES: We investigate the reporting of obesity on death certificates in three countries (France, Italy, and the United States) with different levels of prevalence, and we examine which causes are frequently associated with obesity. METHODS: We use cause-of-death data for all deaths at ages 50–89 in 2010–2011. Since obesity may not be the underlying cause (UC) of death, we compute age- and sex- standardized death rates considering all mentions of obesity (multiple causes or MC). We use cluster analyses to identify patterns of cause-of-death combinations. RESULTS: Obesity is selected as UC in no more than 20% of the deaths with a mention of obesity. Mortality levels, whether measured from the UC or the MC, are weakly related to levels of prevalence. Patterns of cause-of-death combinations are similar across the countries. In addition to strong links with cardiovascular diseases and diabetes, we identify several less familiar associations. CONCLUSIONS: Considering all mentions on the deaths certificates reduces the underestimation of obesity-related mortality based on the UC only. It also enables us to describe the various mortality patterns involving obesity.